Reviewing ensemble methods in Particle Swarm Optimization (PSO) - Dewangan, Pranjali; Sahu, Neelam (International Journal of Psychosocial Rehabilitation, 2020)
The Particle Swarm Optimization algorithm (Particle Swarm Optimization or PSO) [Kennedy and Eberhart, 1995] is a bioinspired algorithm that is based on an analogy with the social behavior of certain species. Two basic influences of inspiration are recognized in PSO: The movement of flocks of birds, in which each individual dis-squares using simple rules for adjusting its speed depending on the observations he makes about the close individuals in the flock. A social model in which each particle represents a belief and influences between individuals the approach of individuals to others by diffusion of said beliefs.